Affluent in the face of poverty : on what rich individuals like us should do - Philips, Joseph Pieter Mathijs, 1974- (Pallas Proefschriften Ser., 2007)
In this time of mass communication, rich people like us know very well the horrible conditions in which many poor people must live. In Affluent in the Face of Poverty Jos Philips wonders what we should do about poverty.